Growth in Labor Earnings Across the Income. Distribution: Latin America During the 2000s - Irene Brambilla; Darío Tortarolo (Universidad Nacional de La Plata, Centro de Estudios Distributivos, Laborales y Sociales (CEDLAS), 2015)
The objective of this paper is to characterize the evolution of labor earnings in Latin America during the 2000s, a decade of markedly poverty reduction. Based on household surveys for six countries, Brazil, Chile, Costa Rica, Ecuador, Honduras and Mexico, we study clusters of increases in labor earnings across worker, job, and industry characteristics. Throughout the analysis we allow for worker income heterogeneity, so as to characterize the evolution of labor earnings across the income distribution. For three of the six countries, we match the household survey data with industrial data from UNIDO and COMTRADE and find that increases in productivity and changes in product composition are more important than industry output as determinants of increases in labor earnings within manufacturing.
Keywords: 330